Evaluation from inside Out: The Experience of Using Local Knowledge and Practices to Evaluate a Program for Adolescent Girls in India through the Lens of Gender and Equity. (March 2015) - Nandi, Rajib; Nanda, Rituu B; Jugran, Tanisha
This article describes an interesting approach where the evaluators recognised the value of using local community knowledge and experience in evaluating a Government of India program for the development and empowerment of adolescent girls. The evaluators tried to integrate participatory and appreciative approaches and looked at the evaluation process through a gender and equity lens. The evaluators went beyond the mandate of evaluation and focused on building evaluation capacity by fostering ownership of the program among stakeholders and encouraging the community to be the active agents of change. Instead of traditional evaluation where evaluators are outsiders, we engaged the stakeholders in the evaluation. All the stakeholders, including the funding agency, a non-government organisation (NGO), the adolescent girls and the wider community were engaged in varying degrees—from defining the objectives, designing questions, data collection and data analysis in the context of their aspirations and expectations, so that it could be an occasion for recognition and celebration of their strengths. The local project implementers and the adolescent girls themselves re-evaluated their own responses and used them in a particular context to further empower themselves. We used principles of the strength-based approach and framed appreciative questions, which recognised the strengths of the community and NGO staff. This created a non-threatening environment, which stimulated open sharing of experiences. Further, this resulted in reinforcing the evaluation process by improving the quality and richness of data that the community produced itself, which would not have been the case in a traditional evaluation. Additionally, a gender and equity lens was used to conduct the evaluation in six multi-ethnic districts, populated with religious and linguistic minorities, and an indigenous population. The gender and equity lens allows recognising the systematic discrimination based on gender, caste and class. The evaluation was able to probe whether the program assessed time, mobility, poverty and accessibility constraints of girls, and accounted for intersectional discrimination.